Comparative Transcriptome and DNA Methylation Analysis of Phenotypic Plasticity in the Pacific Abalone (Haliotis discus hannai) - Huang, Zekun; Xiao, Qizhen; Yu, Feng; Gan, Yang; Lu, Chengkuan; Peng, Wenzhu; Zhang, Yifang; Luo, Xuan; Chen, Nan; You, Weiwei; Ke, Caihuan (Frontiers in Physiology, 2021)
Phenotypic plasticity is an adaptive mechanism used by organisms to cope with environmental ﬂuctuations. Pacific abalone (Haliotis discus hannai) are large-scale farmed in the temperate area of northern China and in the warmer waters of southern China. RNA-seq and comparative transcriptomic analysis here were performed to determine if the northern and southern populations have evolved divergent plasticity and if functional differences are associated with protein synthesis and growth-related biological progress. The DNA methylation (5mC) landscape of H. discus hannai from the two populations using whole genomic bisulfite sequencing (WGBS), exhibited different epigenetic patterns. The southern population had significant genomic hypo-methylation that may have resulted from long-term acclimation to heat stress. Combining 790 differentially expressed genes (DEGs) and 7635 differentially methylated genes (DMGs), we found that methylation within the gene body might be important in predicting abalone gene expression. Genes related to growth, development, transduction, and apoptosis may be regulated by methylation and could explain the phenotypic divergence of H. discus hannai. Our findings not only emphasize the signiﬁcant roles of adaptive plasticity in the acclimation of H. discus hannai to high temperatures but also provide a new understanding of the epigenetic mechanism underlying the phenotypic plasticity in adaptation to climate change for marine organisms.